Analysis of the contribution of the microfibrils and matrix to the deformation processes in wool fibers - Tsobkallo, Katherina; Aksakal, Baki; Darvish, Diana (WILEY-BLACKWELL, 2012)
In this study, the mechanical and structural characteristics of wool fibers were examined, and the contributions of the microfibrils and matrix to the deformation processes were analyzed. The experiments were carried out on single wool fibers. To understand the structural changes at different deformation levels, the wool fibers were treated with a complex mechanical regime. One of the most significant results from the mechanical tests was the estimation of the modulus of the matrix, which changed from 0.07 to 1.6 GPa during stretching. This result proves the proposal of the netlike structure of the matrix. On the basis of the obtained experimental data and the structural model, where the microfibrils and matrix play the role of a reinforcing phase and a filler, respectively, the rigidity of the microfibrils in the initial unstretched state was determined to be equal to about 20 GPa. The experimental data obtained from the Fourier transform infraredattenuated total reflectance spectroscopy method proved the a beta conformational transition both in the yield and postyield regions and revealed the presence of the stable beta form, which was not sensitive to stretching. (C) 2012 Wiley Periodicals, Inc. J Appl Polym Sci, 2012
Keywords: matrix; mechanical properties; structure-property relations; KERATIN FIBERS; RAMAN-SPECTROSCOPY; STRUCTURAL-CHANGES; ALPHA-KERATIN; HUMAN HAIR; MECHANICAL-PROPERTIES; STRETCHED WOOL; WATER; POLYPROPYLENE; TEMPERATURE; Polymer Science